Encyclopedia of new religions: new religious movements, sects and alternative spiritualities - Partridge, Christopher (A Lion book, 2004)
Mainstream orthodox faiths have spawned a host of new religions, sects and alternative spiritualities over the last 100 years. This encyclopedia, written for the non-specialist by an authoritative team of specialist contributors, offers a comprehensive guide to 200 of the most significant ones to have emerged over the last century. Each section begins with an overview of the main tradition from which particular new movements have sprouted. Examples include from Christianity, Christian Science; from Judaism, Messianic Judaism; and from Islam, Bah'ai. Other sections include Buddhism, indigenous and pagan traditions, esoteric and New Age traditions and modern western culture. Throughout the book there are feature articles that deal with groups of these new faiths, key themes surrounding new movements, and particular beliefs and practices popular in contemporary new religions.